2016
DOI: 10.1021/acs.jproteome.6b00713
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Profiling Reveals That Diverse Metabolic Pathways Are Influenced by Melatonin in an in Vivo Model of Ovarian Carcinoma

Abstract: To obtain more information into the molecular mechanisms underlying ovarian cancer (OC), we proposed a comparative proteomic analysis in animals receiving long-term melatonin as therapy or only vehicle using multidimensional protein identification combined with mass spectrometry. To induce tumor, a single dose of 100 μg 7,12-dimethylbenz(a)anthracene (DMBA) dissolved in 10 μL of sesame oil was injected under the left ovarian bursa of 20 Fischer 344 rats. The right ovaries were injected with sesame oil only. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 65 publications
0
42
0
Order By: Relevance
“…Subsequent studies confirmed that the molecular events normally associated with this type of experimental ovarian cancers were reversed by melatonin treatment [230,231,232]. Most recently, quantitative profiling of these tumors verified the broad modulatory actions of melatonin on essential signaling pathways in ovarian cancer cells [233] hinting at the possibility that melatonin should be considered as a therapeutic opportunity for women with this deadly disease. At the clinical level, melatonin has not been used as an adjuvant treatment for ovarian cancer.…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 89%
“…Subsequent studies confirmed that the molecular events normally associated with this type of experimental ovarian cancers were reversed by melatonin treatment [230,231,232]. Most recently, quantitative profiling of these tumors verified the broad modulatory actions of melatonin on essential signaling pathways in ovarian cancer cells [233] hinting at the possibility that melatonin should be considered as a therapeutic opportunity for women with this deadly disease. At the clinical level, melatonin has not been used as an adjuvant treatment for ovarian cancer.…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 89%
“…Also, the cellular metabolic pathways have critical roles in shaping T‐cell development, homeostasis, activation/differentiation, and memory processes . Whether melatonin regulates the biology of T cells through cellular metabolism is of interest as melatonin influences the metabolism of treated subjects . Through modulation of T‐cell responses, melatonin has beneficial actions in various inflammatory diseases, such as T1D, SLE, and MS.…”
Section: Discussionmentioning
confidence: 99%
“…187 Whether melatonin regulates the biology of T cells through cellular metabolism is of interest as melatonin influences the metabolism of treated subjects. 188,189 Through modulation of T-cell responses, melatonin has beneficial actions in various inflammatory diseases, such as T1D, SLE, and MS. However, additional experiments are necessary before its clinical application as a therapeutic or adjuvant therapy can be initiated for treatment of these and other autoimmune diseases.…”
Section: T a B L E 3 Roles Of Melatonin In Threementioning
confidence: 99%
“…Moreover, acetaldehyde originating from ethanol oxidation acts as a co-carcinogenic agent through association with DNA, and by promoting cross-links between pairs of bases G:A and A:T [7,8]. Notably, we have developed a useful ethanol-preferring rat model that strictly reflects the aspects of serous papillary OC after chemical induction with a carcinogen [9,10]; this model provides an appropriate histological and molecular background that is needed to evaluate new chemoprotective compounds.…”
Section: Introductionmentioning
confidence: 99%